Tailoring microstructure of metallic glass for delocalized plasticity by pressure annealing: Forward and inverse studies. (November 2021) - Tang, Y.; Zhao, Q.K.; Zhou, H.F.; Hu, W.; Xu, T.D.; Zheng, L.; Nutor, R.K.; Wang, X.D.; Cao, Q.P.; Zhang, D.X.; Sha, G.; Wang, H.K.; et al.
Abstract: As an extreme processing condition, pressure annealing has a great potential in tailoring the microstructure of metallic materials to improve their mechanical properties. Determining the process-microstructure-mechanical properties relationship with high-pressure and high-temperature is thus of scientific importance. Herein, we propose an approach of pressure annealing in tuning the structure and mechanical behavior of a prototype of Fe80 P20 metallic glass (MG) through a combination of experiments, molecular dynamics (MD) simulations, and machine learning. The experimental results show that pressure annealing can induce structural rejuvenation and more distributed deformation in Fe80 P20 MG. Inspired by this, forward studies from experiments to MD simulations are carried out to systematically investigate the effects of pressure annealing on the mechanical properties and microstructure of the Fe80 P20 MG for a broad pressure and temperature range, followed by inverse studies from machine learning to experimental verification that enable us to capture the hiding structural feature affecting the mechanical behavior of pressure-annealed Fe80 P20 MG. We demonstrate that pressure annealing can endow a MG having a transition of deformation mode from localized to delocalized, which is predominantly governed by pressure-annealing-induced variations in an atomic packing structure. Our work proposes a promising route for fine-tuning the mechanical properties of MGs, and provides insights into the current understanding of the relationship between the microstructure and mechanical behaviors of Fe80 P20 MG with pressure annealing. Graphical abstract: Image, graphical abstract